IL-32 and IL-34 in hepatocellular carcinoma - Si, Yang; Zhang, Jiwei; Bao, Shisan; Wise, Steven G.; Wang, Yuli; Zhang, Yanfang; Tang, Yuhong (Frontiers in Medicine, 2022)
Hepatocellular carcinoma (HCC) remains a major challenge to clinicians due to its unacceptably high mortality and morbidity. The aetiology of HCC is multi-faceted, including viral infection, alcoholism and non-alcoholic fatty liver disease. Dysregulated host immunity contributes to tumorigenesis among these susceptible individuals with pre-existing condition(s). IL 32 and IL-34 are key cytokines driving the development of chronic inflammatory conditions such as rheumatoid arthritis, systemic lupus erythematosus, as well as chronic liver diseases. IL-32 and IL-34 play an important role augmenting the development of HCC, due to their direct influence over host inflammation, however, new roles for these cytokines in HCC are emerging. Here we comprehensively review the latest research for IL-32 and IL-34 in HCC, identifying a subset of potential therapeutic targets for use in precision medicine.